Peningkatan Minat Baca Generasi Z Melalui Kegiatan Biblioterapi di Nagari Padang Lua dan Ladang Laweh, Kecamatan Banuhampu, Kabupaten Agam - Erlianti, Gustina; Marlini, Marlini; Fikry, Zulian (Ilmu Informasi Perpustakaan dan Kearsipan, 2021)
Generation Z's interest in reading is still relatively low when compared to the use of gadgets in their lives. The purpose of this study was to determine the impact of bibliotherapy activities as a medium for solving generation Z problems which later were expected to increase their reading interest in books. This type of research is descriptive qualitative by interviewing five (5) informants from Generation Z in Nagari Padang Lua and Ladang Laweh, Banuhampu District, Agam Regency. From the results of the study, it was stated that there was a positive influence from bibliotherapy activities where those who were busy with their respective gadgets now tend to choose to finish reading the books that have been provided by the research team and discuss the problems they face. The hope is that the love for books can be maintained so that it can become a habit and even the reading culture of Generation Z in Nagari Padang Lua and Ladang Laweh, Banuhampu District, Agam Regency.